Cytotoxicity and exhaustion markers of chimeric antigen receptor T cells targeting BCMA in multiple myeloma cell lines between patients and healthy donors - Prasongtanakij S. (2023)
Objectives: Multiple myeloma (MM) accounts for 10% of hematologic malignancies. However, most of the patients suffered from relapsed/refractory disease. We would like to expand CAR T cell therapy to treat MM using our current platform. Methods: BCMA CAR T lymphocytes were generated for volunteers or MM patients. The transduction efficiency was detected by the ddPCR technique. Immunophenotyping and exhaustion markers were monitored by flow cytometry. The efficacy of BCMA CAR T cells was tested using coculturing with BCMA CAR or mock, and the positive and negative targets, K562/hBCMA-ECTM and K562, respectively. Results: BCMA CAR T cells were generated from consented volunteers or MM patients and could be detected CAR BCMA expression at a mean of 4.07 ± 1.95 or 4.65 ± 1.21 copies/cell, respectively. Those modified T cells were primarily effector memory T cells. Our BCMA CAR T cells could explicitly eradicate the K562/hBCMA-ECTM cell line while the K562 cell line survived. Interestingly, the BCMA CAR, mock T cells, and peripheral blood mononuclear cells from MM patients expressed similar levels of the exhaustion makers, TIM-3, LAG-3, and PD1. Conclusions: Our BCMA CAR T cells, mainly effector/effector memory, could eliminate BCMA-expressing cells in vitro and had similar levels of exhaustion markers among different populations.